Critical Analysis of Protection of Plant Varieties and Farmers Rights in Pakistan under the Plant Breeders’ Rights Act 2016 - Hafiz Aziz-ur-Rehman, Muhammad Mubeen (JSSH, 2024)
The Government of Pakistan passed the Plant Breeders’ Rights Act 2016, the approval of which took more than one and half decade. The bill of the Plant Breeders’ Rights Act was presented for approval several times with amendments. Though, the Act is still considered controversial between the Federal and Provincial governments.